Reimagining an elementary teacher education preparation program: Striving for integrated teaching - Benjamin Boche; Selina Bartels; Douglas Wassilak (Educational Considerations, 2021)
Despite elementary teacher education programs preparing preservice teachers in the main content areas of literacy, math, science, and social studies, few elementary school classrooms teach all four content areas on a regular and thorough basis. Therefore, elementary education teacher preparation programs should be redesigned to support an integrated teaching model of all four content areas in order to better prepare preservice teachers (PST) to serve elementary students. The main research question for this study was "How does a collaborative and integrated elementary education program impact PSTs’ knowledge and understanding of an integrated K-6 elementary classroom?" The sample included 12 preservice education students at a Midwest, private liberal arts university. The study occurred over three semesters in a newly developed integrated elementary education program. Data tools collected included: field experience lesson plans, preservice classroom observations, a survey of experiences, video-recorded lessons, and the edTPA. When looking at the different types of integration, the most common was interdisciplinary teaching where one content area supported the work of another. The lack of integration may be due to limited or no tools available to support preservice teachers to teach in this fashion. To answer the research question, it was found that the PSTs graduated from the preservice program and entered their own classrooms with a vague understanding of integrated teaching. Although our program was integrated in the delivery of content and field experience, the transparency was not revealed to the PSTs during their methods classes and field work.
Keywords: : integrated teaching; integrated methods coursework; elementary education teacher preparation